Counter-terrorism law and returnees: the Belgian legal framework applicable to returnees from war zones in Syria and Iraq - Yperman, Ward (Boomjuridisch, 2023)
"Belgium has one of the highest numbers of Jihadist fighters per capita in Europe. A large group of often young men and women left Belgium for the IS Caliphate in Syria and Iraq. This book focuses on the law governing this situation, with its aim being twofold. First, it provides a comprehensive and detailed overview of the legal framework. Second, it provides suggestions on how to improve the framework, both with a view to effectiveness and with respect for fundamental rights and principles. This book can serve as a valuable source of information for any (legal) practitioner who is confronted with returnees. In addition, any person with an interest in and/or personal experience with the subject will gain a much greater understanding of the situation of returnees based on the legislation applicable to them. This book is part of a BELSPO funded project called Reguide, which aims to develop an integrative and gendered approach for the reintegration of Belgian returnees in society." -- cover page 4